2017
DOI: 10.1002/humu.23255
|View full text |Cite
|
Sign up to set email alerts
|

Postzygotic single‐nucleotide mosaicisms contribute to the etiology of autism spectrum disorder and autistic traits and the origin of mutations

Abstract: The roles and characteristics of postzygotic single‐nucleotide mosaicisms (pSNMs) in autism spectrum disorders (ASDs) remain unclear. In this study of the whole exomes of 2,361 families in the Simons Simplex Collection, we identified 1,248 putative pSNMs in children and 285 de novo SNPs in children with detectable parental mosaicism. Ultra‐deep amplicon resequencing suggested a validation rate of 51%. Analyses of validated pSNMs revealed that missense/loss‐of‐function (LoF) pSNMs with a high mutant allele frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 62 publications
0
77
0
Order By: Relevance
“…Recent researches have significantly expanded what is known about the functional roles of postzygotic mutations, which now include not only cancers and overgrowth disorders [45], but also other complex disorders [11,46]. With the help of next-sequencing technologies, postzygotic mutations have been identified and validated in healthy individuals [13,39], confirming the theoretical predictions that postzygotic mutations are prevalent and every person is a mosaic [23].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Recent researches have significantly expanded what is known about the functional roles of postzygotic mutations, which now include not only cancers and overgrowth disorders [45], but also other complex disorders [11,46]. With the help of next-sequencing technologies, postzygotic mutations have been identified and validated in healthy individuals [13,39], confirming the theoretical predictions that postzygotic mutations are prevalent and every person is a mosaic [23].…”
Section: Discussionmentioning
confidence: 78%
“…Unlike de novo or inherited germline mutations, postzygotic mutations only affect a fraction of cells in multicellular organisms, and individuals carrying a functional mosaic mutation typically exhibit a milder phenotype [3][4][5]. The roles of postzygotic single-nucleotide mosaicisms (pSNMs) have been demonstrated in numerous cancers [6,7] and various types of developmental disorders, including malformations [8,9] and autism [10,11]. We and another research group have reported the first genome-wide identification and characterization of pSNMs from the peripheral blood samples of healthy individuals [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies detected somatic mutations (postzygotic mutations) in the known risk genes for ASD with the allele fractions ≥ 5% in blood cells from patients with ASD. [55][56][57][58] The relevance of the genes and the large allele fractions indicate early occurrence in development, shared between the brain and the blood. The contribution of such somatic mutations to ASD was estimated to be 3-5%.…”
Section: Discussionmentioning
confidence: 99%
“…Post-zygotic mosaic mutations have been implicated in several diseases including non-malignant developmental disorders such as overgrowth syndromes {Poduri 2013; Lindhurst 2012; Kurek 2016}, structural brain malformations {Poduri 2012; Jamuar 2014; Riviere 2012; Lee 2012}, epilepsy {Stosser 2018}, and autism spectrum disorder {Lim 2017; Krupp 2017; Freed 2016; Dou 2017}. Recent analyses also identified mosaic variants in a cohort of patients with congenital heart disease (CHD) {Manheimer 2018}, but the prevalence of these was far less than germline variants (CHD) {Zaidi 2013; Homsy 2015; Jin 2017; Zaidi 2017}.…”
Section: Introductionmentioning
confidence: 99%